Solar Thermal Water Heater Requirements For Typical Malaysian House - Ludan, Shamila Sandhu (2016)
As one of renewable resources of energy, solar energy has great potential to be developed in Malaysia because the country receives 4000- 5000 W/m2 daily radiation and monthly average daily sunshine duration ranging from 4 hours to 8 hours. The utilization of solar energy would reduce dependency on the fossil fuel which its price keeps fluctuating and also creates environmental pollution from emission of greenhouse gas (GHG) such as carbon monoxide, CO and nitrogen oxide, NOx. Solar photovoltaic (PV) and Solar Water Heater (SWH) are examples of solar energy applications that could be used in Malaysia.Solar Water Heater uses solar energy to produce hot water needed in households. The objectives of this study are to simulate the transient heating characteristics of solar thermal collector, to determine optimum design parameters of the solar thermal collector system based on year performance under meteorological data of Penang, Malaysia, to develop a TRNSYS simulation model of the flat plate collector system and to investigate the effects of collector area and mass flow rate on outlet temperature and heat transfer rate of solar collector. Simulation using TRNSYS software had been done to investigate the performance of the solar water heater by using typical meteorological year (TMY) data for Penang, Malaysia. Results obtained from simulations shows that 8m2 solar thermal collector with 70kglhr mass flow rate is the most optimum parameters for the system. This is considering the cost for the solar thermal water heater system. Larger solar collector area will needs more cost for the system. The highest collector outlet temperature was achieved in January, November and December which is 80°C. The heat transfer rate in solar collector also highest in these months ranging from 22500W to 24000W. Increasing in mass flow rate resulting in decreases of collector outlet temperature. This is due to higher volume of water need to be heated with the same amount of solar energy absorbed by .the solar collector. For future research, it is recommended that the study also look into the effect of solar collector tilted angle on the outlet temperature and heat transfer rate, and CFD analysis of the solar collector.Economic analysis of the solar water heater also need to be studied in detail.